Preparation and characterization of chitosan from razor clam shell for absorption of methylene blue - Busu, Nursyamimi (2025)
This research explores the extraction and characterization of chitosan from razor clam shells and its adsorption efficiency for methylene blue (MB) removal. The study addresses the limited availability of razor clams and investigates their potential as an alternative source of chitosan. Chitosan was successfully extracted through demineralization, deproteinization, and deacetylation, achieving a high degree of deacetylation (95.66%). Characterization using Fourier Transform Infrared Spectroscopy (FTIR) confirmed the presence of amine (-NH2) and hydroxyl (-OH) functional groups, essential for adsorption. X-ray Diffraction (XRD) analysis indicated a low crystallinity structure, while Scanning Electron Microscopy (SEM) revealed a fine, fibrous surface morphology, which enhances adsorption properties. CHNS analysis confirmed the elemental composition, validating the purity of the extracted chitosan. Adsorption studies showed 86.8% MB dye removal within 60 min, influenced by hydrogen bonding and electrostatic interactions. The study concludes that razor clam shells are a sustainable and effective source of high-quality chitosan, offering significant potential for wastewater treatment applications.